Integrated metabolomics and gut microbiota analysis to explore the potential mechanism of levo-tetrahydropalmatine against ketamine addiction - Du, Yan; Ma, Qing; Gao, Xingcui; Su, Hongliang; Yun, Keming; Du, Li (Frontiers in Pharmacology, 2025)
IntroductionMetabolic and gut microbiota (GM) disturbance play a significant role in the complex pathogenesis of substance dependence. Although levo-tetrahydropalmatine (l-THP) demonstrates therapeutic potential in drug addiction, the underlying mechanism remains elusive.MethodsThe efficacy of l-THP was assessed using a conditioned place preference (CPP) paradigm. In this research, we combined metabolomics with gut microbiota analysis to investigate the potential mechanisms underlying l-THP’s intervention in ketamine (KET) addiction.ResultsL-THP effectively relieved hippocampus (Hip) pathological changes and attenuated KET-induced rewarding effects. Metabolomic profiling of serum and urine samples revealed a total of 194 distinct metabolites, including 3-methoxytyramine, 3-hydroxyphenylacetic acid, and phosphorylcholine, involving glycerophospholipid metabolism, tyrosine metabolism, phenylalanine metabolism, dopaminergic synapse, teichoic acid biosynthesis, staurosporine biosynthesis, and lysine biosynthesis metabolism pathways. L-THP also enriched Firmicutes, Lactobacillus, Dubosiella, unclassified_Clostridia_UCG_014, and Ligilactobacillus while decreasing the levels of Bacteroidota, Campylobacterota, Patescibacteria, unclassified_Bacilli, UCG_005, Prevotella, and Romboutsia. Moreover, Spearman’s correlation analysis showed that discriminative metabolites were closely correlated with special bacteria.ConclusionThe findings demonstrated that l-THP might serve as a promising intervention strategy for KET addiction by regulating serum and urine metabolism and gut microbiota.